Hydrogen as a Renewable Fuel of Non-Biological Origins in the European Union—The Emerging Market and Regulatory Framework - Andrzej Graczyk; Paweł Brusiło; Alicja Małgorzata Graczyk (Energies)
The European Union continues to lead global efforts toward climate neutrality by developing a cohesive regulatory and market framework for alternative fuels, including renewable hydrogen. This review article critically examines the recent evolution of the EU’s policy landscape specifically for hydrogen as a renewable fuel of non-biological origin (RFNBO), highlighting its growing importance in hard-to-abate sectors such as industry and transportation. We assess the interplay of market-based mechanisms (e.g., EU ETS II), direct mandates (e.g., FuelEU Maritime, RED III), and support auction-based measures (e.g., the European Hydrogen Bank) that collectively shape both the demand and the supply of hydrogen as RFNBO fuel. The article also addresses emerging cost, capacity, and technical barriers—ranging from constrained electrolyzer deployment to complex certification requirements—that hinder large-scale adoption and market rollout. The article aims to discuss advancing and changing regulatory and market environment for the development of infrastructure and market for hydrogen as RFNBO fuel in the EU in 2019–2024. Synthesizing current research and policy developments, we propose targeted recommendations, including enhanced cross-border coordination and capacity-based incentives, to accelerate investment and infrastructure development. This review informs policymakers, industry stakeholders, and researchers on critical success factors for integrating hydrogen as a cornerstone of the EU’s climate neutrality efforts.